Analisa Faktor Kesulitan Mahasiswa Dalam Menyelesaikan Skripsi Dengan Algoritma C4.5 - Azi Arisandi; Irfan Sudahri Damanik; Ilham Syahputra Saragih (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2020)
The purpose of this study was to determine the most dominant factor in students' difficulties in completing their thesis. In this study, researchers used data mining techniques using the C4.5 algorithm. Sources of research data used were obtained from interviews and questionnaires to students randomly in the STIKOM Tunas Bangsa Pematangsiantar environment. The research variables used were motivation to graduate on time (C1), ability to write scientific papers (C2), availability of learning resources (C3), guidance process (C4), and peer environment (C5). In this study, the alternative used as a sample is the student of STIKOM Tunas Bangsa, semester eight. The results of the classification using the C4.5 algorithm and testing with rapidminer software found that the most dominant factor in student difficulty in completing theses was the motivation to graduate on time (C1) with a gain value of 0.204593531.